2017
DOI: 10.1186/s12882-017-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis stimulating agents and reno-protection: a meta-analysis

Abstract: BackgroundErythropoiesis stimulating agents (ESAs) were proposed to enhance survival of renal tissues through direct effects via activation of EPO receptors on renal cells resulting in reduced cell apoptosis, or indirect effects via increased oxygen delivery due to increased numbers of Hb containing red blood cells. Thus through several mechanisms there may be benefit of ESA administration on kidney disease progression and kidney function in renal patients. However conflicting ESA reno-protection outcomes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…Whether identification and treatment of potentially reversible causes of anemia or treatment of anemia can positively influence the risk for recurrent AKI without causing significant adverse effects is unknown. 29 In terms of potentially modifiable risk factors, we found that severe hypertension (ie, systolic blood pressure > 180 mm Hg) was an independent risk factor for recurrent AKI. It has been previously shown that among severely hypertensive individuals, AKI is a common complication and is associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 80%
“…Whether identification and treatment of potentially reversible causes of anemia or treatment of anemia can positively influence the risk for recurrent AKI without causing significant adverse effects is unknown. 29 In terms of potentially modifiable risk factors, we found that severe hypertension (ie, systolic blood pressure > 180 mm Hg) was an independent risk factor for recurrent AKI. It has been previously shown that among severely hypertensive individuals, AKI is a common complication and is associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, in trauma patients EPO could the expected to have some protective effects within 24‐48 hours after injury. Despite experimental and evidence, a lack in positive effects on renal function has been shown in patients undergoing kidney transplantation and in this study, in TBI patients with trauma . It needs to be noted that the renal endpoints we studied, that is, KDIGO although relevant, may be too crude to detect smaller changes in renal function.…”
Section: Discussionmentioning
confidence: 68%
“…Enrolled patients received either weekly doses of 40 000 IU of subcutaneous epoetin alfa (Eprex Janssen‐Cilag Pty Ltd, Titusville, NJ, USA) or placebo (0.9% sodium chloride). The randomization process and administration of drug has been described previously . The administration of EPO continued until patients had received a maximum of three doses, or until the patients was discharged from the ICU .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elliott et al found that EPO-R protein was below the detection limit in tissues and renal cells and no evidence of EPO-R expression and function in the kidneys (33). A subsequent meta-analysis of clinical trials by Elliott et al showed that ESAs had no clear renoprotective effect, at least in the included subjects (34). Thus, it is currently controversial whether functional EPO-R occurs on the plasma membranes of renal cells.…”
Section: Epo and Related Moleculesmentioning
confidence: 99%